The influence of Fintech on Financial Inclusion: An International Study - Feghali, Khalil; Daher, Lama; Nassif, Pamela (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2024)
The digital transformation supported by Fintech firms is rapidly transforming the nature and the shape of the financial markets all over the world, especially after the Covid-19 outbreak and the recent pandemic that have accelerated the implementation and development of these technologies. This disruption on the financial markets is leading to changes in different processes, products and services. Nevertheless, it is argued that the importance of the effect of Fintech is linked to two main factors: including the individuals left out by the financial markets, thus increasing financial inclusion, and benefiting from the decreased trust in the banks. Consequently, we find it valuable to study the relationship between Fintech and financial inclusion. We claim that it is beneficial to study the effect of Fintechs on two different types of financial inclusion, savings and credit, to be able to determine if there will be different or similar consequences. We hypothesize that Fintechs have a positive effect on the inclusion by savings and also a favorable impact on the inclusion by credit. Using cross country data from the World Bank related to the financial inclusion and a Fintech index “Global Fintech index2020”, including the rankings and scores of 65 countries in which more than 7,000 Fintech companies, we find that Fintech is associated with greater financial inclusion.